Oceans 81 1981
DOI: 10.1109/oceans.1981.1151650
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Binding Macromolecules in Intraspecific Marine Microbial Associations

Abstract: High molecular weight exudates that enhance the adhesion of t h e marine ChZoreZZa vulgaris Beij. t o g l a s s h a v e b e e n i s o l a t e d d i r e c t l y f r o m t h e c u l t u r e media of t h i s micro alga and marine bacterial s t r a i n s by iuununoaffinity chromatography. These materials s i g n i f i c a n t l y i n c r e a s e t h e a d h e s i o n of ChZorezkz a t c o n c e n t r a t i o n s o f g / c e l l . The a d h e s i o n a c t i v i t y of e x u d a t e a n t i g e n i s o l a t e d f r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The degree to which starch is accessible in the hydrophobic plastic matrix largely influences the ability of amylolytic bacteria to attach to the plastic surface, as well as availability of starch to hydrolytic enzymes (10,13). Adhesive interactions of microorganisms with insoluble polymeric surfaces is an important phenomenon implicated in a variety of biochemical responses at both a cellular and a molecular level (2,3,7,11,12,15,23,26). It has been suggested that the binding of cellulolytic bacteria to plant cell wall and cellulose matrix facilitate cellulose fiber degradation (4)(5)(6)22).…”
mentioning
confidence: 99%
“…The degree to which starch is accessible in the hydrophobic plastic matrix largely influences the ability of amylolytic bacteria to attach to the plastic surface, as well as availability of starch to hydrolytic enzymes (10,13). Adhesive interactions of microorganisms with insoluble polymeric surfaces is an important phenomenon implicated in a variety of biochemical responses at both a cellular and a molecular level (2,3,7,11,12,15,23,26). It has been suggested that the binding of cellulolytic bacteria to plant cell wall and cellulose matrix facilitate cellulose fiber degradation (4)(5)(6)22).…”
mentioning
confidence: 99%
“…These materials have been recovered from coastal seawater and from cultures of marine algae and bacteria (30,31). In the marine environment, symbiotic associations between microorganisms can be regulated by specific cell surface molecules (12,13).…”
mentioning
confidence: 99%
“…The marine alga Chlorella vulgaris (Beij.) is specifically associated with a gram-positive coccoid bacterium in situ (19;Tosteson et al,in press). Both of these microorganisms produce HMW materials that have a lectin-like activity.…”
mentioning
confidence: 99%
“…MATERIALS AND METHODS HMW exudates produced by microorganisms have been recovered from their laboratory culture media by dialysis (34). In general, the concentrations of HMW exudate materials recovered from these laboratory cultures ranged from nanograms to micrograms per milliliter of cell-free medium (19,34). To facilitate the isolation of the microbial exudates examined in this study and reduce the time required, we used immunological techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation